A Discourse Analysis on Deixis Used in “Night Changes” Song by One Direction - Jon Salvator Adhi Keo; Agustinus Simamora; Meliana Br. Siahaan; Carolin Panjaitand; Rahel Manik; Herman Herman (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study is to conduct an analysis and determine which deixis are present in the song